Influence of Dynamic Capability, Market Research, and Social Capital on Marketing Sustainability and Competitiveness of Tourism Creative Economy in Indonesia - Wijayanto, Gatot; Jushermi, Jushermi; Nursanti, Aida; Pramadewi, Arwinence; Novandalina, Arini; Rivai, Yutiandry (IJBLE Scientific Publications Community Inc., 2024)
This study explores how market research, social capital, and dynamic capabilities interact to shape the competitiveness and sustainability of firms in Indonesia's tourism creative economy. Survey data from 215 businesses were analyzed quantitatively using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings show a strong correlation between dynamic capability and competitiveness and sustainability in marketing. Likewise, social capital and market research showed favorable correlations with competitiveness and sustainability in marketing. While the structural model attained good fit indices, the measurement model proved to be valid and reliable. These results advance our knowledge of the variables affecting competitiveness and sustainable marketing strategies in the fast-paced environment of the tourism creative economy.